Flood Hazard Mapping in the Babura Sub-Watershed Using the Geomorphic Flood Index (GFI) Approach - Hasanul Arifin Purba; Rizky Franchitika (Lembaga Riset Ilmiah, 2025)
This study aims to map flood hazard areas in the Babura Sub-Watershed, Medan City, using the Geomorphic Flood Index (GFI) approach based on topographic data. The method was selected as an alternative under conditions of limited hydrological and hydraulic data by utilizing a Digital Elevation Model (DEM) and derived analyses, including flow direction and flow accumulation. The analytical process involved DEM preprocessing, geomorphological parameter calculation, and spatial classification of flood hazard levels. The results show that the GFI method successfully identified several high flood susceptibility zones, particularly around Jalan Kapiten Purba, Jalan Pintu Air IV, Kwala Bekala, J-City Housing, and parts of the Citra Wisata residential area, which correspond well with actual flood events recorded during the Medan flood in November 2025. However, discrepancies were also observed in certain downstream areas, such as the Soewondo Air Base, where the model indicated high susceptibility despite limited actual flood occurrence. These differences highlight limitations of the geomorphological approach, particularly its inability to account for hydraulic processes, infrastructure conditions, and land-use influences in detail. Despite these limitations, the GFI method proved to be a rapid and cost-efficient tool for generating preliminary flood hazard maps, making it a reliable initial approach for understanding potential flood inundation patterns and supporting flood mitigation planning and risk management.